The Effect of Students’ Responsiveness Toward Teachers’ Role in Indonesian Language Learning on Reading Interest of Grade XI Students - Harsri Wiyati; Sujarwoko Sujarwoko; Moch. Muarifin (Jurnal Ilmiah Multidisiplin, 2026)
This study examines the effect of student responsiveness and the role of Indonesian language teachers on the reading interest of Grade XI students at SMK Negeri 2 Kediri in the 2025/2026 academic year. A quantitative approach with a multiple linear regression design was applied. The sample consisted of 100 students selected using cluster sampling. Data were collected through a structured questionnaire containing 30 items measuring student responsiveness (X1), teacher role (X2), and reading interest (Y). The data were analyzed using SPSS version 25, including validity, reliability, classical assumption tests, multiple regression analysis, coefficient of determination, and hypothesis testing. The results show that all instruments were valid and reliable. Partial testing indicates that student responsiveness significantly influences reading interest (t = 6.104; p < 0.001), while teacher role also has a significant effect (t = 5.393; p < 0.001). Simultaneously, both variables significantly affect reading interest (F = 92.624; p < 0.001). The coefficient of determination (R² = 0.656) indicates that 65.6% of reading interest is explained by the two variables, while 34.4% is influenced by other factors. These findings emphasize the importance of active student engagement and effective teacher roles in improving students’ reading interest in vocational education contexts.